2013
DOI: 10.1371/journal.pone.0062148
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low Density Lipoprotein Induced Caspase-1 Mediated Pyroptotic Cell Death in Macrophages: Implication in Lesion Instability?

Abstract: BackgroundMacrophage death in advanced lesion has been confirmed to play an important role in plaque instability. However, the mechanism underlying lesion macrophage death still remains largely unknown.Methods and ResultsImmunohistochemistry showed that caspase-1 activated in advanced lesion and co-located with macrophages and TUNEL positive reaction. In in-vitro experiments showed that ox-LDL induced caspase-1 activation and this activation was required for ox-LDL induced macrophages lysis, IL-1β and IL-18 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 34 publications
2
61
1
1
Order By: Relevance
“…Our results also indicated that p65 was activated by ox-LDL, and p65 activation was Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry required for IL-1β production. In addition to IL-1β gene and protein expressions, ox-LDL also promoted its maturation (showed by cleaved IL-1β), which is similar to previous results [35,36]. Caspase-1 is the major regulator that promote IL-1β maturation and is mainly regulated by NLRP3 [37].…”
Section: Discussionsupporting
confidence: 88%
“…Our results also indicated that p65 was activated by ox-LDL, and p65 activation was Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry required for IL-1β production. In addition to IL-1β gene and protein expressions, ox-LDL also promoted its maturation (showed by cleaved IL-1β), which is similar to previous results [35,36]. Caspase-1 is the major regulator that promote IL-1β maturation and is mainly regulated by NLRP3 [37].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, pre‐treatment with a caspase‐1 inhibitor (Z‐YVAD‐FMK) clearly attenuated PA‐induced cell death; therefore, PA‐mediated cytotoxicity partially owed to the induction of pyroptosis. Importantly, mature IL‐1β is one of the key proinflammatory cytokine implicated in many human diseases, including diabetes , AS and neurodegenerative diseases , and ICAM‐1 expression is important for the initiation and progression of AS . Thus, in the present study, we also demonstrated that PA induced IL‐1β maturation and release, as well as ICAM‐1 expression in HUVECs, which were attenuated by Z‐YVAD‐FMK.…”
Section: Discussionmentioning
confidence: 99%
“…Although apoptosis is well documented in atherosclerosis, recent studies showed that pyroptosis also plays an important role in atherosclerosis and plaque stability . Pyroptosis is a caspase‐1‐dependent apoptotic process characterized by the presence of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%